Faktor-Faktor Yang Mempengaruhi Niat Beli Mobil Low-Cost Green Car (LCGC) Di Kota Lhokseumawe - Safrida, Safrida Safrida; Heriyana, Heriyana Heriyana; ., Samsul Bahri; Nurainun, Nurainun Nurainun (Jurnal Visioner & Strategis, 2024)
This research aims to determine the influence of individual factors, social media advertising and brand image on purchasing behavior for Honda Scoopy brand motorbikes in West Aceh Regency (Meulaboh). The data collection used in this research is primary data obtained by distributing questionnaires directly and via Google Form to 125 respondents. The data analysis technique used is a multiple linear regression analysis technique using SPSS version 26 software. The results of the research show that individual factors, social media advertising and brand image have a positive and significant effect on purchasing behavior for Honda Scoopy brand motorbikes in West Aceh Regency (Meulaboh). Based on analysis of the coefficient of determination, an R value of 0.890 was obtained, which shows that the relationship between all individual factor variables, social media advertising and brand image, and purchasing behavior is quite strong. The R Square value is 0.792, which indicates that 79% of purchasing behavior variables can be explained by individual factor variables and social media advertising. while 21% was influenced by other variables not included in this study. Keywords: Individual factors, social media advertising, brand image and purchasing behavior